The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14202/vetworld.2016.1043-1046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding guar meal on nutrient utilization and growth performance in Mahbubnagar local kids

Abstract: Aim:This study was conducted to evaluate the growth performance and nutrient digestibility of guar meal, an unconventional protein-rich feed ingredient in kids in comparison to conventional groundnut cake.Materials and Methods:A total of 18 kids were randomly allotted to three groups, and T1 group was fed on basal diet, T2 and T3 groups were offered diet replacing groundnut cake at 50% and 100% with guar meal, respectively, for a period of 120-day. At the end of the growth trial, a digestibility trial was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Another study revealed optimum inclusion level at 50 g/ kg of sprouted guar than roasted guar bean meal suggested beneficial for growth in broiler diets (Madzimure et al, 2017). A study of Janampet et al (2016) confirmed that the inclusion of 50% guar meal instead of groundnut cake enhanced the growth rate and digestion coefficient of nutrients without any adverse effects on performance. No significant difference was observed in the growth performance among guar meal groups.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation
“…Another study revealed optimum inclusion level at 50 g/ kg of sprouted guar than roasted guar bean meal suggested beneficial for growth in broiler diets (Madzimure et al, 2017). A study of Janampet et al (2016) confirmed that the inclusion of 50% guar meal instead of groundnut cake enhanced the growth rate and digestion coefficient of nutrients without any adverse effects on performance. No significant difference was observed in the growth performance among guar meal groups.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 90%
“…Fairly higher CP contents like 45.9%, 36.9%, and 38.5% have been reported in guar germ, hull, and combined guar by-products, respectively (Lee et al, 2004). Recently, the percentage of DM, organic matter (OM), CP, EE, CF, nitrogen-free extract (NFE), ash, acid detergent fiber and neutral detergent fiber for guar meal were 93.56, 94.66, 49.52, 3.59, 4.46, 37.09, 5.35, 22.59 and 44.05 respectively, on DM basis ( Janampet et al, 2016). Chemical compositions of GM and SBM are explained in Table 1.…”
Section: Trade and Global Production Of Guarmentioning
confidence: 99%
“…Guar or cluster bean, with the botanical name Cyamopsis tetragonoloba drought tolerant legume grown in the Rajasthan state of India. Guar meal is a protein and fiber rich nutritional food for livestock containing germ and hull part of it (Janampet et al, 2016). Rajasthan produces Guar crop 2,204,931 tons annually in 2014-15.…”
Section: Organic Waste Generationmentioning
confidence: 99%
“…The guar bean (Cyamopsis tetragonoloba) is an annual legume belonging to the Fabaceae family, which native to Africa, and now mainly produced in India and Pakistan (Pach and Nagel, 2018). Guar meal (GM) is a byproduct from guar gum industry, obtained after mechanical separation of endosperm from both germ and hull of guar seed (Janampet et al, 2016;Reddy et al, 2017). GM contains approximately 30-60 % protein on dry matter basis (Nidhina and Muthukumar, 2015;Janampet et al, 2016;Reddy et al, 2017;Pach and Nagel, 2018) and its amino acid (AA) composition quite similar to that of ground nut cake (Verma and McNab, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Guar meal (GM) is a byproduct from guar gum industry, obtained after mechanical separation of endosperm from both germ and hull of guar seed (Janampet et al, 2016;Reddy et al, 2017). GM contains approximately 30-60 % protein on dry matter basis (Nidhina and Muthukumar, 2015;Janampet et al, 2016;Reddy et al, 2017;Pach and Nagel, 2018) and its amino acid (AA) composition quite similar to that of ground nut cake (Verma and McNab, 1984). It seems that GM is a desirable and viable protein source for animal feed formulators, especially when the rocketing prices of feed raw material.…”
Section: Introductionmentioning
confidence: 99%